2002
DOI: 10.1097/01.asn.0000025786.87646.b1
|View full text |Cite
|
Sign up to set email alerts
|

PPAR Agonists Amplify iNOS Expression While Inhibiting NF-κB

Abstract: Abstract. In acute inflammation, the transcription factor NF-B is activated and increases the expression of multiple proinflammatory genes. Agonists of peroxisome proliferator activated receptors (PPAR) have been reported to exert antiinflammatory effects in various systems. In keeping with such an antiinflammatory role, it was found that several PPAR agonists, including Wy14,643, clofibrate, carbaprostacyclin, and ciglitazone inhibited NF-B activity and increased IB␣ levels in cytokine-stimulated mesangial ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(35 citation statements)
references
References 46 publications
2
32
1
Order By: Relevance
“…There are, however, only two previous reports on the effects of PPARa agonists on iNOS expression and NO production in macrophages showing contradictory results (Colville-Nash et al, 1998;Cernuda-Morolló n et al, 2002). Colville-Nash et al (1998) found that a selective PPARa ligand WY14643 reduced interferon-g and LPS-induced NO production in RAW 264.7 macrophages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are, however, only two previous reports on the effects of PPARa agonists on iNOS expression and NO production in macrophages showing contradictory results (Colville-Nash et al, 1998;Cernuda-Morolló n et al, 2002). Colville-Nash et al (1998) found that a selective PPARa ligand WY14643 reduced interferon-g and LPS-induced NO production in RAW 264.7 macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…PPARg agonists were proposed to inhibit the action of inflammatory transcription factors nuclear factor kappa B (NF-kB), activator protein 1 and signal transducer and activator of transcription 1 (STAT1) (Ricote et al, 1998;Chen et al, 2003). The effects of PPARa agonists on NO production and iNOS expression in macrophages have been less studied (Colville-Nash et al, 1998;Cernuda-Morolló n et al, 2002). The results of the two studies were contradictory and the mechanisms of action were not investigated in detail.…”
Section: Introductionmentioning
confidence: 99%
“…Again, this hypothesis will be tested in the future. The controversy about whether RAW264.7 macrophages indeed express PPARg has been settled by showing that these cells express PPARg mRNA 30 and protein 31 as well as its activation in response to LPS/IFNg. 32 Our data on EMSA analysis, reporter activity and elimination of PPARg effects by transduction of a d/n PPARg mutant corroborated these findings.…”
Section: Discussionmentioning
confidence: 99%
“…Rat MC were obtained as reported earlier (18). Cells were grown in RPMI 1640 supplemented with 10% FBS, 2 mM glutamine, 100 U/ml penicillin, and 100 g/ml streptomycin.…”
Section: Cell Culturementioning
confidence: 99%